St. Vincent and the Grenadines : 2009 Article IV Consultation and Request for Disbursement Under the Rapid-Access Component of the Exogenous Shocks Facility; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for St. Vincent and the Grenadines. (IMF Staff Country Reports; Country Report, 2009)
St. Vincent and the Grenadines's financial system has been largely unaffected by the global financial crisis. The report examines St. Vincent and the Grenadines 2009 Article IV Consultation and request for Disbursement under the Rapid-Access Component of the Exogenous Shocks Facility. The global economic downturn has led to a significant decline in tourism, which worsened the balance of payments position and, together with lower foreign direct investment and construction activity, led to a sharp output slowdown in 2008.